Use of Inner Preputial Flap and Buck’s Fascia Versus Buck’s Fascia Only During Coronal and Subcoronal Hypospadias Repair - Dawre, Anik; Chowdhury, Tahmina Akhter; Al Farooq, Md Abdullah; Chowdhury, Tanvir Kabir (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Reconstructive surgery for hypospadias is very challenging with multiple complications. Hence several approaches were addressed. To strengthen neourethra second and third layer of vascular tissue flaps are tried. The aim of the present study was to compare the outcome between inner preputial flap and Buck’s fascia covering with Buck’s fascia only covering over neourethra in coronal and subcoronal hypospadias. Materials and methods: This was a quasi-experimental study conducted at Department of Paediatric Surgery in Chittagong Medical College Hospital, Chattogram from June 2021 to September 2023. A total of 32 patients of coronal and subcoronal hypospadias aged below 12 years with urethral plate >8 mm wide were included in this study. The even number patients were used both preputial flap and Buck’s fascia (n =16) for covering andodd number patients (n 2 1 =16) were treated with only Buck’s fascia. Postoperative wound infection, wound dehiscence, urinary stream, Urethrocutaneous (U-C) fistula and meatal stenosis during 3 consecutive follow up were compared. Results: The median age of the patients in inner preputial flap and Buck’s fascia group and only Buck’s fascia were 5.5 and 7 years respectively. In both preputial flap and Buck’s fascia group 14 (87.5%) had coronal hypospadias and 2 (12.5%) patients had subcoronal hypospadias. In Buck’s fascia group, 12 (75.0%) had coronal hypospadias while 4 (25.0%) patients had sub-coronal hypospadias. Inbothinner preputial flap and Buck’s fascia group, 5 (31.3%) patients had spray of urinary stream postoperatively whilein the Buck’s fascia group, 3 (18.8%) patients had spray of urinary stream postoperatively (p=0.685). Among the 16 patients in both preputial flap and Buck’s fascia group, 5 (31.3%) developed UC fistula while among the 16 patients in the Buck’s fascia group, 3 (18.8%) developed UC fistula (p=0.685). None of the patients in either group developed wound infection, wound dehiscence or meatal stenosis. Conclusion: For coronal and subcoronal hypospadias additional inner preputial flap does not significantly improve outcome than single layer cover by Buck’s fascia over neourethra. JCMCTA 2025 ; 36 (1) : 97-101